2022
DOI: 10.20944/preprints202211.0353.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relationship between Association between Blood Pressure and Risk of Cancer Development

Abstract: Background of the Study: We investigated the link between hypertension and cancer since it has been suggested that hypertension may raise the long-term risk of cancer. Previous large observational cohort studies found that greater blood pressure (BP) was related to a higher risk of cancer. Mendelian randomization (MR) was utilized to produce less confounded blood pressure estimates (BP) on overall and site-specific malignancies. The study aims to draw conclusions on the relationship between high blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Others refer to patients being treated or having been treated some months before measurement [30,[33][34][35]. With regard to cancer survivors, differences have been found with respect to some aspects of life: marital status, the number of infants and insurance facilities for patients with Hodgkin's Disease (28); satisfaction with costs of living, taxes, national government and leisure activities for patients having been radiated [29]; psychosocial complaints, malaise, satisfaction with sleep, physical condition and life as a whole for patients having undergone chemotherapy [20), health concerns and self control [31 J and physical disability C32] in mixed patient groups. However, no differences were found with respect to most QL indicators: satisfaction with family, friends, work, income, values, activities, community, local government, health and the overall quality of life [29 J, psychological functioning [32], anxiety, depression, positive wellbeing, mental and general well-being [31 J, daily activities [20] and work rehabilitation [28).…”
Section: Comparison Q/ Cancer Patients and Other Groups Oj Patients O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Others refer to patients being treated or having been treated some months before measurement [30,[33][34][35]. With regard to cancer survivors, differences have been found with respect to some aspects of life: marital status, the number of infants and insurance facilities for patients with Hodgkin's Disease (28); satisfaction with costs of living, taxes, national government and leisure activities for patients having been radiated [29]; psychosocial complaints, malaise, satisfaction with sleep, physical condition and life as a whole for patients having undergone chemotherapy [20), health concerns and self control [31 J and physical disability C32] in mixed patient groups. However, no differences were found with respect to most QL indicators: satisfaction with family, friends, work, income, values, activities, community, local government, health and the overall quality of life [29 J, psychological functioning [32], anxiety, depression, positive wellbeing, mental and general well-being [31 J, daily activities [20] and work rehabilitation [28).…”
Section: Comparison Q/ Cancer Patients and Other Groups Oj Patients O...mentioning
confidence: 99%
“…However, no differences were found with respect to most QL indicators: satisfaction with family, friends, work, income, values, activities, community, local government, health and the overall quality of life [29 J, psychological functioning [32], anxiety, depression, positive wellbeing, mental and general well-being [31 J, daily activities [20] and work rehabilitation [28). Interestingly enough, survived cancer patients even seemed more satisfied with care from the partner and others than healthy controls are [20]. As in the studies referring to patients being treated more recently, the results look similar.…”
Section: Comparison Q/ Cancer Patients and Other Groups Oj Patients O...mentioning
confidence: 99%
“…The development of cancer prevention and treatment techniques may benefit from understanding the pathophysiological mechanisms underlying the link between obesity and malignancy. A group of researchers found that obesity can lead to hypertension which also increases cancer risk (Tzenios, Tazanios, & Chahine, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Some Cardiovascular diseases represent France, as in many other developed countries, a major public health issue. Hypertension Arterial hypertension (HTA) is the most common modifiable cardiovascular risk factor [1,2]. Specific recommendation ns on its detection and management charge have been enacted for a decade by different learned societies.…”
Section: Introductionmentioning
confidence: 99%